2016
DOI: 10.1080/14764172.2016.1225963
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of platelet-rich plasma in the treatment of androgenetic (male-patterned) alopecia: A pilot randomized controlled trial

Abstract: Our study showed that the PRP was not effective in treating AGA of grade 4-6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 24 publications
0
85
0
1
Order By: Relevance
“…Two studies noticed greater improvement in lower-grade AGA [27,32], while one noted increased improvement in higher-grade AGA [36]. Only one study, by Mapar et al [31], concluded that PRP was not effective in treating AGA through analysis of terminal and vellus hair count. However, in this study, only 2 treatments were administered, and outcomes were assessed under magnifying glass, which may not be the best method to measure results.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies noticed greater improvement in lower-grade AGA [27,32], while one noted increased improvement in higher-grade AGA [36]. Only one study, by Mapar et al [31], concluded that PRP was not effective in treating AGA through analysis of terminal and vellus hair count. However, in this study, only 2 treatments were administered, and outcomes were assessed under magnifying glass, which may not be the best method to measure results.…”
Section: Discussionmentioning
confidence: 99%
“…With the initial PRP preparation, there is a lack of consensus regarding the mode of preparation, addition of activators, centrifugation time and speed, platelet concentration attained, and volume of blood and PRP used (Table 3). Three studies, for example, used calcium chloride as an activator [12,33,35], while 2 studies used calcium gluconate [31,27], 1 study used PRGF activator [29], and 2 other studies did not specify the chemical that provided Ca 2+ [28,34]. Treatment protocols also varied in the number of sessions, time interval between treatments, administration procedure, and follow-up period (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations